THE ROLE OF ETHICS IN AUDITING: ENSURING ACCOUNTABILITY AND INTEGRITY IN THE COMMUNICATION COMPANIES IN INDONESIA AND THE GAMBIA - Drammeh, Lamin K; kholmi, Dr, Masiyah; Malik, Prof. Nazaruddin (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
In this research, we examine the antecedent of ethics in auditing with a focus on The Gambia and Indonesia’s communication sectors emphasizing its potential of eradicating bad deeds by instating regulations, training, and culture. It is crucial to have ethical auditing for an organization to always be transparent, have the organization’s stakeholders trust it, and follow the law especially when the policies are ever changing. The study uses an ethical theoretical framework comprising of competence, objectivity, integrity, and confidentiality in an analysis of secondary information from company records and other literature. The study shows that technical auditing promotes responsibility and scores ethical points, but faces obstacles, including limited resources, political influence, technology advancement. As a solution to these challenges that needs to be implemented to improve the public trust in the communication sector, the study recommends the following; Boosting up of the regulations, Training of the auditors, and creation of an ethical tone.